2015
DOI: 10.1055/s-0035-1564609
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Stem Cells in the Etiology and Pathophysiology of Endometriosis

Abstract: Human endometrium is a dynamic organ that normally undergoes repetitive cyclic regeneration. To enable this rapid regeneration, it is not surprising that the endometrium contains a reservoir of progenitor stem cells. However, this pool of cells that allows the growth of the endometrium also allows for unrestrained growth that can reach beyond the endometrium. In this review, we will address the role of stem cells in endometriosis. Recent characterization of stem cell populations within human endometrium has op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
78
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(83 citation statements)
references
References 77 publications
0
78
0
2
Order By: Relevance
“…14,15 Knapp postulated that endometriosis is caused by small defects of embryogenesis. Mullerian duct maldevelopment during embryogenesis could cause the spread of endometriotic cells across the posterior pelvic floor and the persistence of embryonic cell rests.…”
Section: Makiyanmentioning
confidence: 99%
“…14,15 Knapp postulated that endometriosis is caused by small defects of embryogenesis. Mullerian duct maldevelopment during embryogenesis could cause the spread of endometriotic cells across the posterior pelvic floor and the persistence of embryonic cell rests.…”
Section: Makiyanmentioning
confidence: 99%
“…The receptive state of the secretory endometria is vital for the proper implantation of embryo, and abnormal physiological conditions would cause miscarriage (Cakmak and Taylor 2011). On the other hand, the shedding endometrial pellets of the secretory endometria would lead to serious pathological outcomes under certain circumstances, like endometriosis, when the shedding endometrial pellets go reversely along the oviduct into the abdominal cavity (Hufnagel et al 2015). However, the precise regulatory mechanisms for the preparation of the secretory uterus for embryo implantation and etiology of endometriosis remains unclear (Hufnagel et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Endometrial stem/progenitor cells were shown to be involved in the regeneration of the damaged functional layer during the menstrual cycle (Gargett, Nguyen, and Ye 2012) and continuous growth upon embryo implantation, as well as involved in the pathological process of endometriosis (Hufnagel et al 2015). However, the precise identify, function and regulatory mechanisms of the uterus epithelial stem/progenitors during these physiological and pathological circumstances in vivo remains unclear (Valentijn et al 2013;Gargett, Schwab, and Deane 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Although the etiology is not fully characterized, endometriosis is a multifactorial disorder, resulting from retrograde menstruation, ectopic differentiation of stem cells, dysregulated immune/inflammatory responses, aberrant expression of multiple genes, and exposure to environmental factors. [2][3][4][5][6][7][8] Various cellular mechanisms are activated, which allow survival, adhesion, proliferation, and invasion of endometrial cells that reach the peritoneal cavity. 9,10 The development of endometriosis involves altered activation of immune factors that induce a permissive environment leading to the survival of endometrial cells ectopically.…”
Section: Introductionmentioning
confidence: 99%